Inhibitory effect of lactobacillusfrom fermented foods and drinks on porphyromonas gingivalis / Anis Mardhiyah Mazlan, Farida Zuraina Mohd Yusof and Siti Saizah Md Said - Mazlan, Anis Mardhiyah; Mohd Yusof, Farida Zuraina; Md Said, Siti Saizah (Universiti Teknologi MARA Cawangan Pahang, 2018)
Lactobacillus spp. are potential lactic acid bacteria in improving periodontal health. In the present study, Lactobacillus spp. were isolated from cheese, commercial milk, yogurt, pickle and tempeh. A total of 41 isolates were identified with biochemical tests and were used to antagonize a periodontal pathogen, Porphyromonas gingivalis ATCC 33277. The inhibitory study was investigated through agar well diffusion method. All isolates were able to inhibit the growth of P. gingivalis. One-way ANOVA shows that there was statistical significance difference among the isolates Lactobacillus species where the p=0.02. Isolate L. plantarumshowed the highest inhibition (12.33+0.88 mm) whereas isolatesL. reuteri and L. suebicusexhibited the least inhibitions on P. gingivalis (9.83+0.17 mm). All isolates were further identified using 16S rDNA gene identification. Based on the comparison of biochemical tests and 16S rDNA identification, the 41 isolates can be known as L. rhamnosus, L. plantarum, L. paracasei, L. fermentumand L. suebicus. In conclusion, this inhibitory study proved that the presence of Lactobacillus in foods and drinks may be an alternative for the prevention of oral disease.